Total synthesis of (+/-)-petasitolone and (+/-)-fukinone - Pasikanti, Srinivas; Reddy, D. Srinivasa; Iqbal, Javed; Dubey, Pramod Kumar; Das, Parthasarathi (Synthesis-Stuttgart, 2009)
An efficient, general, and fully stereocontrolled synthesis of eremophilane-type compounds is disclosed. The approach features a highly diastereoselective Diels-Alder/aldol sequence to give a common intermediate, which is subsequently exploited to produce (+/-)-petasitolone and (+/-)-fukinone in a short sequence.